(untitled) (Journal of Natural Language and Linguistics, 2024)
This phenomenological study delved into the lived experiences of Filipino Generation Z (Gen Z) regarding their language identity in the digital age. The study tries to understand how Filipino Gen Z navigates and develops their linguistic identity in the context of modern ideas and the usage of the Filipino language, given the increasing influence of global media and the rapid growth of communication technologies. Using in-depth interviews with 15 purposively selected participants, the themes provide vital insights into how Filipino Gen Z negotiates their cultural and linguistic identity as global interconnection and technological innovations change communication landscapes. Themes included the influence of social media on language preferences, the role of education in shaping linguistic identity, the impact of global media, and participants’ reflections on the intersection between contemporary philosophies and their linguistic choices. The findings help better comprehend the complex interplay between emerging communication paradigms, contemporary philosophical influences, and the preservation of language legacy in the dynamic setting of the digital era.